2018
DOI: 10.1038/s41467-018-05296-0
|View full text |Cite
|
Sign up to set email alerts
|

Spin-induced multiferroicity in the binary perovskite manganite Mn2O3

Abstract: The ABO3 perovskite oxides exhibit a wide range of interesting physical phenomena remaining in the focus of extensive scientific investigations and various industrial applications. In order to form a perovskite structure, the cations occupying the A and B positions in the lattice, as a rule, should be different. Nevertheless, the unique binary perovskite manganite Mn2O3 containing the same element in both A and B positions can be synthesized under high-pressure high-temperature conditions. Here, we show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…Recently, we have explored the multiferroics and ME coupling in -Mn 2 O 3 [14]. Cong et al also observed spin induced multiferroicity in the high temperature and high pressure phase -Mn 2 O 3 [17]. The pristine -Mn 2 O 3 is orthorhombic at room temperature [18,14] and undergoes cubic to orthorhombic transition at 308 K [19,20].…”
mentioning
confidence: 99%
“…Recently, we have explored the multiferroics and ME coupling in -Mn 2 O 3 [14]. Cong et al also observed spin induced multiferroicity in the high temperature and high pressure phase -Mn 2 O 3 [17]. The pristine -Mn 2 O 3 is orthorhombic at room temperature [18,14] and undergoes cubic to orthorhombic transition at 308 K [19,20].…”
mentioning
confidence: 99%
“…These observations are similar to the measured results on Ni 3 V 2 O 8 and MWO 4 , and the existence of multiple multiferroic phases may be utilized for unusual ME memory applications [ 53 , 54 ]. A long list of other type-II multiferroics, including α-NaFeO 2 [ 55 ], Mn 2 O 3 [ 56 ], (La, Bi)Mn 3 Cr 4 O 12 [ 57 , 58 ], Ni 3 TeO 6 [ 59 , 60 ], (Fe, Mn) 2 Mo 3 O 8 [ 61–63 ], Co 4 Nb 2 O 9 [ 64 ], Mn 2 MnWO 6 [ 65 ], RFe 3 (BO 3 ) 4 [ 66–68 ], KCu 3 As 2 O 7 (OD) 3 [ 69 ], NaFeSi 2 O 6 [ 70 ], In 2 NiMnO 6 [ 71 ], and so on. Certainly, this list should not exclude materials other than oxides, and compounds with other anions such as S and Se have been revealed to show type-II multiferroicity too, including CaOFeS [ 72 ], MnSb 2 S 4 [ 73 ], BaFe 2 Se 3 [ 74 ], Cu 3 Bi(SeO 3 ) 2 O 2 Cl [ 75 ], CsCuCl 3 [ 76 ], and CuBr 2 [ 77 ].…”
Section: Type-ii Multiferroicsmentioning
confidence: 99%
“…Transition metal oxides (TMOs) are a material class with abundant and novel physical properties, such as superconductivity, [1] multiferroicity, [2,3] magnetoresistance, [4] and others. Within TMOs, transition metal ions are in the form of tetrahedrons (BO4) or octahedrons (BO6) due to the different valence states of the cations and/or the concentration of oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%